Characterization of wheat cultivars for pre-harvest sprouting - Bainotti, C.=700 1 Cuniberti, M.; Masiero, B.; Donaire, G.; Gomez, D.; Reartes, F.; Salines, J.; Formica, M.; Fraschina, J.; Nisi, J.; Mir, L.; Berra, O.
(Es, En)
Ilus., 12 ref.
Keywords: TRITICUM SATIVUM; BROTACION; CARACTERISTICAS AGRONOMICAS; ARGENTINA; AGRISCIENTIA